EFFECT OF SOAKING WITH GIBBERELLIC ACID AND SPRAYING WITH HUMIC ACID AND SEAWEED EXTRACT IN SOME FLOWERING CHARACTERISTICS OF GLADIOLUS CV. CHINON - Saleh, Mostafa Abdel Samad; El Sheikhly, Abdel Rahman Abdel Qader (Journal of agricultural, environmental and veterinary sciences, 2018)
The experiment was conducted at research station of horticulture and landscape department / Agriculture college / Diyala university for the period from 1/11/2016 to 1/6/2017. The objectives of experiment to inverstigate the effect of Corms soaking by gibberellic acid at concentrations of(0، 100، 200)mg. L-1، sprayed with three levels of humic acid (0، 0. 3، 0. 5)gm. L-1 and two levels of seaweed extract (0، 0. 5)mg. L-1 for three times second-leaf stage، fourth-leaf stage and sixth-leaf stage on some flowering characteristics. Soaking by gibberellic acid results in significant effect in all studied characteristics، soaking by 100 mg. L-1 had best results regarding period for basal floret opening 118. 670day، inflorescence length 46. 339cm، inflorescence diameter 156. 181mm، spike length 85. 640cm and spike fresh weight 57. 714gm، while soaking by 200 mg. L-1 led to best in basal floret 106. 861mm، number of florets. inflorescence-1 13. 084floret and vase life for wilting 50% of florets per spike. Spraying with 0. 3 gm. L-1 humic acid led to best results in period for basal floret opening 117. 606day، basal floret diameter 103. 742mm and inflorescence diameter 155. 445mm. Spraying with 0. 5 gm. L-1 humic acid had significant effect in inflorescence length 45. 805cm، spike length 85. 407cm and spike fresh weight 56. 331 gm. Spraying seaweed extract led to best results in period for basal floret opening 120. 003day، spike length 84. 904cm and spike fresh weight 56. 331gm. Interactions between the studied factors had significant effect in all studied characteristics except interaction between humic acid and seaweed extract in number of florets. inflorescence-1.